Viscosity and ultrasonic attenuation in 4 He below 0.6 K - Adamenko, Chung-In; Pandey, Soo-Young; George, Sahng-Kyoon; Yoo, T. F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
Through a treatment of three-phonon processes, the wide-angle scattering rates and the absorption rates of phonons, which characterize viscosity and ultrasonic attenuation, respectively, are calculated for 4He below 0.6K. These rates are obtained from the collision matrix which is constructed approximately from an integral eigenvalue equation for the collision operator. The sequence of the lowest eigenvalues of the collision matrix, as the angular momentum quantum number l increases, shows a saturated behavior which has not been reported before. The calculated viscosity and ultrasonic attenuation are compared with previous theoretical and experimental results.